Modelling green entrepreneurial intention among university students using the entrepreneurial event and cultural values theory. (2nd August 2019) - Ramayah, T.; Rahman, Syed Abidur; Taghizadeh, Seyedeh Khadijeh
Going green has created significant enthusiasm across the society. However, green entrepreneurial intention is still at evolving stage. The main objective of this study is to reveal the association of entrepreneurial event theory and cultural values theory with the green entrepreneurial intention. Cross sectional survey was conducted through structured questionnaire among the university students. Partial least squares method has been adopted using the SmartPLS 3.0 software for analysing the data from 835 respondents. The findings of the results revealed that perceived desirability, perceived feasibility, opportunity seeking, and reasonability taking plays significant role for green entrepreneurial intention. The result of the study will provide the governments to explore opportunities for the green entrepreneurial ventures among universities. Universities may offer customised academic courses, or training program to trigger the green business initiative among the students. Students will be benefited to learn the essentials of green entrepreneurial intention from this research.